COSMETICS SALES SYSTEM "WARDAH" IN THE TRADITION OF MOTHER PT.PUSAKA USING MICROSOFT VISUAL BASIC 6.0 - Sulistyorini Sulistyorini; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2008)
The writing is about selling information on the PT. Heritage Tradition Mother, for cosmetics sales system "Wardah" an increasingly widespread that many consumers are interested in the product, until eventually the production process is less well coordinated to meet the buyer's order is experiencing difficulties and obstacles. Under these circumstances, the writer makes a system by referring to the procedure that runs the system is expected to assist in overcoming any problems that exist, in order to improve efficiency and productivity in the manufacture of products that match consumer desires at. Heritage Tradition Mother.